Tìm x biết
x mũ 15 = x
(x-5)4=(x-5)6
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) \(\Rightarrow x^2\left(x^{2004}-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x^{2004}=1\end{matrix}\right.\)\(\Rightarrow\left[{}\begin{matrix}x=0\\x=1\\x=-1\end{matrix}\right.\)
2) \(\Rightarrow\left(x-5\right)^4\left[\left(x-5\right)^2-1\right]=0\)
\(\Rightarrow\left[{}\begin{matrix}x-5=0\\\left(x-5\right)^2=1\end{matrix}\right.\)\(\Rightarrow\left[{}\begin{matrix}x=5\\x-5=1\\x-5=-1\end{matrix}\right.\)\(\Rightarrow\left[{}\begin{matrix}x=5\\x=6\\x=4\end{matrix}\right.\)
2x . 4 = 128
2x = 128 : 4
2x = 32
2x = 2 . 2 . 2 . 2 . 2
2x = 25
x = 5
(2x + 1)3 = 125
(2x + 1)3 = 5 . 5 . 5
(2x + 1)3 = 53
2x + 1 = 5
2x = 5 - 1
2x = 4
x = 4 : 2
x = 2
x15 = x
x = 1
(x - 5)4 = (x - 5)6
x = 6
\(x^{20}=x\\ \Leftrightarrow x^{20}-x=0\\ \Leftrightarrow x\left(x^{19}-1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)
Ta có:
\(x^4=y^4\)
\(\Rightarrow x^4-y^4=0\)
\(\Rightarrow\left(x^2\right)^2-\left(y^2\right)^2=0\)
\(\Rightarrow\left(x^2-y^2\right)\left(x^2+y^2\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x^2-y^2=0\\x^2+y^2=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x-y=0\\x+y=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=y\\x=-y\end{matrix}\right.\)
_______________
Ta có:
\(x^5=y^5\)
\(\Rightarrow x^5-y^5=0\)
\(\Rightarrow x-y=0\)
\(\Rightarrow x=y\)
a) 7.x - x = 521 : 519 + 3.22 - 70
6x = 25 + 12 - 1
6x = 36
x = 6
b) 7x - 2x = 617 : 615 + 44 : 11
5x = 36 + 4
5x = 40
x = 8
c) 5x + x = 39 - 311 : 39
6x = 39 - 9
6x = 30
x = 5
d) [(6x - 39) : 7]. 4 = 12
(6x - 39) : 7 = 12 : 4
(6x - 39) : 7 = 3
6x - 39 = 3 . 7
6x - 39 = 21
6x = 21 + 39
6x = 60
x = 10
x =
\(A=5\cdot4^{15}\cdot9^9-4\cdot3^{20}\cdot8^9\)
\(A=5\cdot\left(2^2\right)^{15}\cdot\left(3^2\right)^9-2^2\cdot3^{20}\cdot\left(2^3\right)^9\)
\(A=5\cdot2^{30}\cdot3^{18}-2^2\cdot3^{20}\cdot2^{27}\)
\(A=5\cdot2^{30}\cdot3^{18}-2^{29}\cdot3^{20}\)
\(A=2^{29}\cdot3^{18}\cdot\left(5\cdot2^1\cdot1-1\cdot3^2\right)\)
\(A=2^{29}\cdot3^{18}\cdot\left(5-9\right)\)
\(A=-2^2\cdot2^{29}\cdot3^{18}\)
\(A=-2^{31}\cdot3^{18}\)
_______________
\(B=5\cdot2^9\cdot6^{19}-7\cdot2^{29}\cdot27^6\)
\(B=5\cdot2^9\cdot2^{19}\cdot3^{19}-7\cdot2^{29}\cdot\left(3^3\right)^6\)
\(B=5\cdot2^{28}\cdot3^{19}-7\cdot2^{29}\cdot3^{18}\)
\(B=2^{28}\cdot3^{18}\cdot\left(5\cdot1\cdot3-7\cdot2\cdot1\right)\)
\(B=2^{28}\cdot3^{18}\cdot\left(15-14\right)\)
\(B=2^{28}\cdot3^{18}\)
Ta có: \(A:B\)
\(=\left(-2^{31}\cdot3^{18}\right):\left(2^{28}\cdot3^{18}\right)\)
\(=\left(-2^{31}:2^{28}\right)\cdot\left(3^{18}:3^{18}\right)\)
\(=-2^3\cdot1\)
\(=-8\)
x=1 vì x mũ 1 lyoon luôn bằng 1
x=1 hoặc0 vì mũ15=0
mà1 mũ15=1